2006
DOI: 10.3310/hta10290
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the clinical and cost-effectiveness of pulmonary artery catheters in patient management in intensive care: a systematic review and a randomised controlled trial

Abstract: Non-UK purchasers will have to pay a small fee for post and packing. For European countries the cost is £2 per monograph and for the rest of the world £3 per monograph.You can order HTA monographs from our Despatch Agents:-fax (with credit card or official purchase order) -post (with credit card or official purchase order or cheque) -phone during office hours (credit card only).Additionally the HTA website allows you either to pay securely by credit card or to print out your order and then post or fax it. NHS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
47
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 32 publications
1
47
0
Order By: Relevance
“…The mean time horizon for the withintrial component of the economic evaluations in the remaining 18 studies was 8 months (median 9 months and range 1 to 12 months). Some studies extrapolated outcomes beyond the trial follow-up period using decision analytic modelling methods [25,26,28] with up to 60 months [25] and lifetime [15,16,28,29] extrapolations beyond the study follow-up periods. Most economic evaluations were conducted from the perspective of the UK National Health Service (NHS) (n=4) or the NHS/Personal Social services (n=9) in accordance with NICE guidance for appraising health technologies [30].…”
Section: Summary Of Rcts Included In the Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…The mean time horizon for the withintrial component of the economic evaluations in the remaining 18 studies was 8 months (median 9 months and range 1 to 12 months). Some studies extrapolated outcomes beyond the trial follow-up period using decision analytic modelling methods [25,26,28] with up to 60 months [25] and lifetime [15,16,28,29] extrapolations beyond the study follow-up periods. Most economic evaluations were conducted from the perspective of the UK National Health Service (NHS) (n=4) or the NHS/Personal Social services (n=9) in accordance with NICE guidance for appraising health technologies [30].…”
Section: Summary Of Rcts Included In the Reviewmentioning
confidence: 99%
“…Most of the economic evaluations did not discount costs and effects in line with the relatively short time horizons of the within-trial analyses. Where studies had extrapolated cost and effects beyond the trial follow-up, discount rates of between 3.0% [25] and 3.5% [16,28,29,33] per annum were applied to both costs and effects. In terms of study quality, all 19 (100%) studies reported using a randomisation process that was assessed as adequate according to the criteria described in Appendix B in the supplementary online material; 16 (84%) were un-blinded and 9 (47%) reported ≥80% completion rates for the primary outcome at end of follow-up.…”
Section: Summary Of Rcts Included In the Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…What is the solution to this dilemma? Every technologic development of a device is based on the central fundamental value of the technique used [15]. On the other hand, a huge development (bubble) may represent an increase or rise over that fundamental value.…”
mentioning
confidence: 99%